(3x)(x-7)=0

Divide each term in (3x)(x-7)=0 by 3.

(3x)(x-7)3=03

Cancel the common factor.

3x(x-7)3=03

Divide (x)(x-7) by 1.

(x)(x-7)=03

(x)(x-7)=03

Divide 0 by 3.

(x)(x-7)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x=0

x-7=0

Set the first factor equal to 0.

x=0

Set the next factor equal to 0.

x-7=0

Add 7 to both sides of the equation.

x=7

x=7

The final solution is all the values that make (3x)(x-7)3=03 true.

x=0,7

Solve Using the Square Root Property (3x)(x-7)=0